The Relationship Of Mother's Level Of Knowledge And Support Husband With Successful Breastfeeding On Babies Aged 0-6 Months In The Work Area Uptd Puskesmas Langsa City: The Relationship Of Mother's Level Of Knowledge And Support Husband With Successful Breastfeeding On Babies Aged 0-6 Months In The Work Area Uptd Puskesmas Langsa City - Melvawaty Purba; Verawaty Fitrinelda Silaban; Despri Noviati; Handariani; Lia Susanti (JURNAL KESMAS DAN GIZI (JKG), 2025)
Breast milk (ASI) is the optimal nutrition for infants up to six months, benefiting both babies and mothers. This study examined the relationship between maternal knowledge and husband’s support with breastfeeding success among mothers of 0–6-month-old infants in the Langsa City Health Center UPTD Work Area. Using a cross-sectional design, 62 respondents were selected through purposive sampling. Data were analyzed using chi-square tests. Most mothers had either poor or good knowledge (33.9%) and received low support from their husbands (64.5%). Breastfeeding was unsuccessful in 72.6% of cases. Maternal knowledge (p=0.002) and husband’s support (p=0.001) were significantly associated with breastfeeding success. In conclusion, maternal knowledge and husband’s support influence successful breastfeeding in the study population